(untitled) (Perner’s Contacts, 2010)
The submission defines a problem of pricing in general cargo by impact of toll in the first part. A different usage of the vehicle in individual transportation causes that it is not possible to calculated the toll uniformly for all cargos by constant price for customer in same transportation keeping. In the rest part is a draft of the new method of toll share for general transport determination processed.